2020
DOI: 10.1155/2020/2602918
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravitreal Injection of Biosimilar of Aflibercept in Rabbit Eyes

Abstract: Purpose. To assess the safety of biosimilar intravitreal aflibercept (CinnaGen Co., Iran) compared to the reference product (Eylea®; Bayer Schweiz AG, Zurich, Switzerland) in rabbit eyes through functional and histologic studies. Methods. Forty New Zealand albino rabbits were recruited to the study and were divided into four groups to be sacrificed at 48 hours, one, two, and four weeks after injections. In each group, five rabbits received 0.05 mL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…At the end of exposure and wash-out time, however, no reduction compared to baseline measurements could be detected. Short-term animal studies have not found retinal toxicity with ERG in the retina of rabbits with aflibercept at 4-week or ziv-aflibercept at 2-week follow-up [36,37]. Six-month and 1-year follow-up of 15 eyes of nAMD patients treated with ziv-aflibercept have not shown signs of toxicity on ffERG [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…At the end of exposure and wash-out time, however, no reduction compared to baseline measurements could be detected. Short-term animal studies have not found retinal toxicity with ERG in the retina of rabbits with aflibercept at 4-week or ziv-aflibercept at 2-week follow-up [36,37]. Six-month and 1-year follow-up of 15 eyes of nAMD patients treated with ziv-aflibercept have not shown signs of toxicity on ffERG [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary in vitro studies have shown that the concentration of 1000 μg/mL of Aflibercept does not show cytotoxic effects in the cell lines of primary cultures of human trabecular meshwork cells, human scleral fibroblasts, and a retinal pigment epithelial cell line [ 24 ]. In vivo studies in rabbit eyes have suggested that short-term administration of Aflibercept does not cause eye irritation [ 25 ]. On the other hand, a 6-month clinical trial found that intravitreal administration of Aflibercept may cause corneal endothelial alterations, but these potential side effects have not been studied in detail [ 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The aforesaid concentration is consistent to the peak of serum concentration of Aflibercept (Cmax) in vivo and after the first intravitreal injection would mimics its systemic effect reasonably. Cmax is obtained by investigating recent anti–VEGF‐associated studies that evaluated the expression level of specific genes on vascular endothelial cells 47‐52 . RNA extraction was performed from HUVEC cells that had been treated 6 hours or 24 hours by Aflibercept (Bayer, Germany) or phosphate‐buffered saline (PBS, as a control).…”
Section: Methodsmentioning
confidence: 99%